SEBARAN TENGKAWANG (Shorea spp.) BERDASARKAN FITOGEOGRAFI PADA HUTAN ADAT PENGAJIT DESA SAHAN KECAMATAN SELUAS KABUPATEN BENGKAYANG - Tampubolon, Sugiarti; Manurung, Togar Fernando; Latifah, Siti (JURNAL HUTAN LESTARI, 2018)
Tengkawang (Shorea spp) is a type of plant that is protected and classified as a type of meranti with tengkawang fat-producing fruit. The spread of tengkawang is usually clustered and grows in tropical rain forests with high rainfall in wet climates and high humidity. This study aims to determine the distribution of tengkawang tree species based on geographical distribution (phytogeography). The study was carried out in the Pengajit village of Sahan customary forest, Seluas District, Bengkayang Regency. The research was conducted by survey method, sampling was carried out by means of a census which is exploring the observation area. Data analysis was carried out by recording data on tengkawang tree types and observations in the form of local names, scientific names, altitude, slope, coordinate points, slope direction (East, West, North and South) and tree diameter. The results of the study were 5 (five) types of tengkawang, namely tengkawang tempiras (Shorea macrophylla Ashton), tengkawang layar (Shorea mecistopteryx Ridl), tengkawang tungkul (Shorea stenoptera Burck), tengkawang air (Shorea seminis Sloot) and tengkawang pengampeng (Shorea pinanga Scheff) with distribution patterns clustered and not clustered. Tengkawang is available at an altitude of <100 m above sea level namely tengkawangpengampeng (Shorea pinanga Scheff), height between 100 - 150 m above sea level, there is tengkawang tempiras (Shorea macrophylla Ashton), tengkawang layar (Shorea mecistopteryx Ridl), tengkawang tungkul (Shorea stenoptera Burck), tengkawang air (Shorea seminis Sloot) and tengkawang pengampeng (Shorea pinanga Scheff) and at altitudes >150 found tengkawang sails (Shorea mecistopteryx Ridl) and tengkawang pengampeng (Shorea pinanga Scheff).Â Keywords: Bengkayang, Customary Forest, Fitogeography, Tengkawang